Nondiscrimination Rules and the Distribution of Fringe Benefits - Carrington, William J.; McCue, Kristin; Pierce, Brooks (Journal of Labor Economics, 2002)
This article considers the impact of nondiscrimination (ND) rules in the federal tax code. Nondiscrimination rules limit within‐firm inequality in the provision on nonwage benefits, but they place no corresponding limit on within‐firm inequality in wages. Firms can skirt ND rules by moving workers with unusual benefits into part‐time and seasonal positions because workers in such positions are excluded from some ND compliance calculations. We examine these issues empirically and find relationships consistent with the hypothesis that ND rules provide a binding constrain on within‐firms benefits inequality.